Reflections on the first of the University CORE courses: A journey of transformation and my intended career in nursing - Cunha, Raquel E. (Young Scholars Grinchenko – Seton International Journal, 2025)
We have explored many ideas and made connections to our individual experiences, allowing us to broaden our thinking. We have thoroughly discussed the importance of higher education, even though the components often seem irrelevant to many college students. We have shared our individual opinions about the importance and relevance of higher education, and I have realized that knowledge is power. Success begins with intelligence and an open mind. While not all aspects of college may seem necessary, they prove essential in the future as they provide us with a learned capacity for broad ideas with room for further thought. My journey as a nursing major has many connections to the real-world application of science and compassion with the human experience. I have discovered a strong link between my future goals in nursing and the ethical, philosophical, and religious subjects we have studied thus far in the course. Plato's Apology and Allegory of the Cave, Msgr. Fahd's Presidential Address, Nostra Aetate, and the Bhagavad Gita are just a few of the texts that have expanded my knowledge of the importance of compassion, empathy, and individual values in the healing process. These concepts highlight the importance of moral integrity, cultural sensitivity, and compassion not only in my future career as a nurse but also in broadening my outlook on the world, which aids in developing my identity as a well-rounded individual.